2017
DOI: 10.18781/r.mex.fit.1703-3
|View full text |Cite
|
Sign up to set email alerts
|

Extractos de Larrea tridentata como una estrategia ecológica contra Fusarium oxysporum radicis-lycopersici en plantas de tomate bajo condiciones de invernadero

Abstract: Resumen. Se Abstract. The antifungal ability of extracts of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
3
0
2
Order By: Relevance
“…They used a 10-day-long extraction method that turned out to be less efficient and effective than ultrasound-microwave technology, which achieves extraction in 20 minutes and with a more controlled and efficient mass transfer. There are reports of complete inhibition of Fusarium growth using extracts from tarbush, however, these results were against F. oxysporum (Peñuelas et al, 2017).…”
Section: Inhibición De Fusarium Y Alternaria Por Polifenoles De Gober...mentioning
confidence: 89%
See 1 more Smart Citation
“…They used a 10-day-long extraction method that turned out to be less efficient and effective than ultrasound-microwave technology, which achieves extraction in 20 minutes and with a more controlled and efficient mass transfer. There are reports of complete inhibition of Fusarium growth using extracts from tarbush, however, these results were against F. oxysporum (Peñuelas et al, 2017).…”
Section: Inhibición De Fusarium Y Alternaria Por Polifenoles De Gober...mentioning
confidence: 89%
“…Esto puede ser explicado por el método (extracción Soxhlet) y disolvente (metanol) empleados por Gamboa-Alvarado et al (2003), quienes utilizaron un sistema de extracción con una duración de 10 días, el cual resulta ser menos eficiente y efectivo que la tecnología de ultrasonido-microondas, que logra la extracción en 20 minutos y con una transferencia de masa más controlada y eficiente. Hay reportes de inhibición completa de Fusarium utilizando extractos de hojasén, sin embargo, estos reportes son contra F. oxysporum (Peñuelas et al, 2017).…”
Section: Inhibición De Fusarium Y Alternaria Por Polifenoles De Gober...unclassified
“…Peñuelas-Rubio et al (2015) [ 75 ] reported that L. tridentata ethanolic and dichloromethane extracts inhibited fungal growth 75–100% against Alternaria tenuissima , Aspergillus niger , Penicillium polonicum and Rhizopus oryzae . In a similar study, ethanolic and dichloromethane extracts inhibited Fusarium oxysporum radicis-lycopersici 100%, while methanolic extract achieved 94% [ 76 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In this sense, a variety of secondary metabolites and diverse compounds of aqueous and ethanolic fractions with antifungal activity have been described (18). However, despite the promising field of research on medicinal extracts with antimicrobial properties for agriculture (11,24,34), most of the ethnobotanical and biological heritage of BCS medicinal plants has focused on their potential use on bacteria and yeasts of clinical interest (12,26).…”
Section: Introductionmentioning
confidence: 99%